2016
DOI: 10.1037/hop0000015
|View full text |Cite
|
Sign up to set email alerts
|

From secure dependency to attachment: Mary Ainsworth’s integration of Blatz’s security theory into Bowlby’s attachment theory.

Abstract: John Bowlby is generally regarded as the founder of attachment theory, with the help of Mary Ainsworth. Through her Uganda and Baltimore studies Ainsworth provided empirical evidence for attachment theory, and she contributed the notion of the secure base and exploratory behavior, the Strange Situation Procedure and its classification system, and the notion of maternal sensitivity. On closer scrutiny, many of these contributions appear to be heavily influenced by William Blatz and his security theory. Even tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 57 publications
(70 reference statements)
1
29
0
1
Order By: Relevance
“…According to Bowlby's attachment theory, human infants need a positive relationship with their caregivers to develop into healthy individuals (Rosmalen, Horst, & Veer, 2016). A negative relationship, in addition to dealing with parental unavailability or unresponsiveness, may contribute to aberrant behavior.…”
Section: Personal Experiences -Attachment Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bowlby's attachment theory, human infants need a positive relationship with their caregivers to develop into healthy individuals (Rosmalen, Horst, & Veer, 2016). A negative relationship, in addition to dealing with parental unavailability or unresponsiveness, may contribute to aberrant behavior.…”
Section: Personal Experiences -Attachment Securitymentioning
confidence: 99%
“…When children observe violence between parents, they learn that violence is an acceptable or effective means for resolving conflicts (Rosmalen, et al, 2016). An earlier study by Kaufman and Ziegler (1987) reported that 30% of individuals who witnessed violence during their childhood become violent in their adulthood.…”
Section: Personal Experiences -Attachment Securitymentioning
confidence: 99%
“…Ainsworth (born Salter in 1918) had completed her undergraduate and graduate training in the Department of Psychology at the University of Toronto, conducting research under the supervision of William E. Blatz (1895–1964), Canadian psychologist and first director of the Institute of Child Study at the University of Toronto. While an assistant professor in the Department of Psychology, Blatz had been in charge of a longitudinal study on the development and social “adjustment” of normal children in a laboratory nursery (Van Rosmalen, Van der Horst, & Van der Veer, ). Funded by the Canadian National Committee for Mental Hygiene and Laura Spelman Rockefeller Memorial, Blatz's research project was one of the first empirical longitudinal studies of child development in North America, which was inspired by the Child Study Movement of G. Stanley Hall (1896–1924) and his followers in American psychology.…”
Section: Separation Research 1948–1956mentioning
confidence: 99%
“…Funded by the Canadian National Committee for Mental Hygiene and Laura Spelman Rockefeller Memorial, Blatz's research project was one of the first empirical longitudinal studies of child development in North America, which was inspired by the Child Study Movement of G. Stanley Hall (1896–1924) and his followers in American psychology. During the 1920s and 1930s, Blatz had continued to carry out prospective examinations of children's social adjustments and lectured on topics that would posthumously published and recognized as his “security theory” (Van Rosmalen, Van der Veer, & Van der Horst, ; Van Rosmalen, Van der Horst, & Van der Veer, ).…”
Section: Separation Research 1948–1956mentioning
confidence: 99%
See 1 more Smart Citation